Accounting for technical efficiency differentials among smallholder tobacco farmers in Hurungwe Zimbabwe : impact of self-selection bias on contract participation - Mungatana, Eric D. (University of Pretoria, 2019)
Dissertation (MSc (Agric))--University of Pretoria, 2018.